2014
DOI: 10.1155/2014/412437
|View full text |Cite
|
Sign up to set email alerts
|

Acute Toxicity and Determination of the Active Constituents of Aqueous Extract ofUncaria tomentosaBark inHyphessobrycon eques

Abstract: Uncaria tomentosa is a medicinal plant used in folk medicine by Amazon tribes. In this study the constituents of aqueous extract of U. tomentosa bark were quantified by chromatographic technique and its lethal concentration 50 (48 h) in Hyphessobrycon eques was determined. The chromatography showed high levels of oxindole alkaloids, quinovic acid glycosides, and low molecular weight polyphenols. The CL50 48 h was 1816 mg/L. Fish showed behavior changes at concentrations above 2000 mg/L, accompanied by a signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Bioactive constituents of U. tomentosa extracts include proanthocyanidins (proanthocyanidin B2 or epicatechin-(4 β ⟶ 8)-epicatechin, the main component; proanthocyanidin B4, proanthocyanidin C1, an epicatechin trimer, epiafzelechin-4 β ⟶ 8-epicatechin, and an epicatechin tetramer) [ 13 ], oxindole alkaloids (isopteropodine, pteropodine, rhynchophylline, mytraphylline, speciophylline, uncarine F, and uncarine E) [ 14 ], indole alkaloidal glucosides (cadambine, 3-dihydrocadambine, and 3-isodihydrocadambine) [ 15 , 16 ], quinovic acid glycosides, tannins, polyphenols, catechins, beta-sitosterol, and proteins which individually or synergistically contribute to their therapeutic properties [ 8 , 17 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bioactive constituents of U. tomentosa extracts include proanthocyanidins (proanthocyanidin B2 or epicatechin-(4 β ⟶ 8)-epicatechin, the main component; proanthocyanidin B4, proanthocyanidin C1, an epicatechin trimer, epiafzelechin-4 β ⟶ 8-epicatechin, and an epicatechin tetramer) [ 13 ], oxindole alkaloids (isopteropodine, pteropodine, rhynchophylline, mytraphylline, speciophylline, uncarine F, and uncarine E) [ 14 ], indole alkaloidal glucosides (cadambine, 3-dihydrocadambine, and 3-isodihydrocadambine) [ 15 , 16 ], quinovic acid glycosides, tannins, polyphenols, catechins, beta-sitosterol, and proteins which individually or synergistically contribute to their therapeutic properties [ 8 , 17 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies in the fish model demonstrated dietary supplementation of U. tomentosa enhanced the immune activity and growth performance [71]. In this case, the most important bioactive compounds found in this plant were oxindole alkaloids, derivatives of quinovic acid glycosides, and low molecular weight polyphenols [72], while our PA-E is composed of proanthocyanidins. Therefore, results on this extract and its nanoformulations F-1 and F-2, constitute to our knowledge, the first report on this DTH activity due to proanthocyanidins present in U. tomentosa leaves and further, according to our findings, the immune response to the antigen is augmented when these compounds are nanoformulated in F-1 and F-2 samples.…”
Section: Evaluation Of the Cellular Immune Response Of Mice Through Dthmentioning
confidence: 61%
“…Serum biochemistry results suggested that camu camu extract has no toxicological action in fish [18]. However, it is necessary further studies using higher concentration of the plant extract to affirm this statement [42].…”
Section: Discussionmentioning
confidence: 99%